2017
DOI: 10.1111/jocd.12364
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional study of the microbiological safety profile of reusing hyaluronic acid fillers

Abstract: Hyaluronic acid fillers did not show any fungal or bacterial contamination after being opened and stored at room temperature in nonaseptic conditions. The possibility of reusing the remaining portion of the material in the syringe can be safe and economically viable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The two earlier studies that examined refrigerated collagen syringes showed growth of mainly skin flora such as Propionibacterium acnes and Staphylococcus epidermidis. Four out of the six microbiological studies that examined hyaluronic acid products showed no growth, using aerobic, anaerobic, and/or fungal culture media . The remaining two microbiological studies that examined hyaluronic acid products showed growth of skin/oral flora in less than 15% of the samples .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The two earlier studies that examined refrigerated collagen syringes showed growth of mainly skin flora such as Propionibacterium acnes and Staphylococcus epidermidis. Four out of the six microbiological studies that examined hyaluronic acid products showed no growth, using aerobic, anaerobic, and/or fungal culture media . The remaining two microbiological studies that examined hyaluronic acid products showed growth of skin/oral flora in less than 15% of the samples .…”
Section: Resultsmentioning
confidence: 96%
“…The details of the included studies are shown in Table . Seven of the nine studies examined hyaluronic acid products while two studies examined collagen fillers . Few samples of calcium hydroxylapatite were included in one study .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies and reviews found no evidence of contamination associated with reused HA gel fillers regardless of concentration and original injection site and no correlation between length of storage time and contamination risk. 1,2,[11][12][13] Storage in original syringes at room temperature in nonaseptic conditions for up to 12 months likely increases the risk. 11 Regarding direct evidence of contamination-related adverse effects in injected individuals, a somewhat dated retrospective review reported no infection in the only subject-based study that looked for adverse events among individuals injected with HA from stored filler syringes.…”
Section: Discussionmentioning
confidence: 99%